Exploring the Antecedents of Safety Performance for Malaysian Construction Industry : A Conceptual Framework - Mohammad Fazley Hossain, Bin Chowdhury; Rusli, Bin Ahmad (American Journal of Trade and Policy (AJTP), 2018)
This conceptual paper intends to present as a proposition of a framework to understand the antecedents of safety performance behaviors. The elements of performance which refer to the tangible behaviors exhibited by individuals at work, safety participation and safety compliance, are crucial in maintaining safe workplace for construction industry. This article illustrates potential antecedents in determining safety performance behaviors as effect of safety leadership attributes and safety climate components based on the Wu et al. (2008) model and current literature in this field. The article contributes to a better understanding of safety situation in the construction industry through the relationships among safety leadership behaviors, safety climate components and safety performance behaviors. This paper ends with a suggestion of the conceptual framework to study the antecedents of safety performance in the context of Malaysian construction industries.